2021
DOI: 10.1002/ags3.12514
|View full text |Cite
|
Sign up to set email alerts
|

Germline Variants in DNA Damage Repair Genes: An Emerging Role in the Era of Precision Medicine in Pancreatic Adenocarcinoma

Abstract: Pancreatic adenocarcinoma is a lethal disease that is projected to become the second most common cause of cancer deaths by 2030. The role of adjuvant therapy after surgical resection has been established by several clinical trials to prolong survival and improve outcomes. Multiagent chemotherapy seems to be the most promising approach to counteract early recurrence and improve survival; however, in the era of precision medicine, patient selection and individualized therapy seems to hold the key to desirable su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…WES is a high-throughput technology that allows the sequencing of almost all protein-coding genes of the human genome. 43,44 Our results showed that an SNP in R3HCC1 (c.919G > A, rs2272761) was useful as a biomarker of hematotoxicity, such as severe neutropenia, in patients who received irinotecan-containing doublet chemotherapy (i.e., FOLFIRI) for mCRC. R3HCC1 may be a useful biomarker for irinotecan-related toxicity in addition to UGT1A polymorphisms (Table 4).…”
Section: Discussionmentioning
confidence: 81%
“…WES is a high-throughput technology that allows the sequencing of almost all protein-coding genes of the human genome. 43,44 Our results showed that an SNP in R3HCC1 (c.919G > A, rs2272761) was useful as a biomarker of hematotoxicity, such as severe neutropenia, in patients who received irinotecan-containing doublet chemotherapy (i.e., FOLFIRI) for mCRC. R3HCC1 may be a useful biomarker for irinotecan-related toxicity in addition to UGT1A polymorphisms (Table 4).…”
Section: Discussionmentioning
confidence: 81%
“…PARPi prevents repair of SSB by trapping PARP enzymes on DNA, creating a stall in the replication fork and converting the SSB into a DSB. 282 , 289 While normal cells without HDR mutations are able to repair the induced DSB via HDR, HDR‐deficient cells are unable to repair the DSB in an error‐free way, leading to accumulation of DNA errors and eventual tumor cell death. 291 Several different PARPi (Olaparib, Velaparib, and Rucaparib) have been developed and tested over the past few years with promising results.…”
Section: Next Generation Sequencing and Targeted Therapymentioning
confidence: 99%
“…These genes encode for key proteins in homology‐directed repair (HDR), which is an error‐free repair system for DNA double strand breaks (DSB) 280,281 . When loss of function mutations occur in one or more of these genes, HDR is impaired, and cells become more reliant on nonhomologous end joining and other DSB repair systems, which are more error prone 282 . Previous studies have reported that HDR‐mutated ovarian and breast cancers are more susceptible to drugs that induce DSB, such as platinum‐based chemotherapy 283–285 .…”
Section: Next Generation Sequencing and Targeted Therapymentioning
confidence: 99%
See 2 more Smart Citations